The sandbeetle : a novel. - Rohan, Zina. (London : Flamingo, 1994)
Leo Beck, a Jewish child refugee, is sent alone to London in the early 1930s. A young man when war eventually breaks out, he is caught up in a wave of anti-German feeling and involved in a voyage of terror and brutal self-discovery. Rohan is also writing here about the nature of belonging.
Keywords: World War, 1939-1945 -- Great Britain -- Fiction; World War, 1939-1945 -- Fiction. -- Jews; Jews -- Great Britain -- Fiction